A schwannoma of superficial radial nerve in hand clinically masquerading a subcutaneous lipoma: a very rare case report - Bhat, Tanveer Ahmad; Alokaili, Hisham; Alkadi, Renad O.; Altamimi, Abdulla S.; Mirza, Mohammed Y. (International Surgery Journal, 2023)
Schwannoma also called neurilemmoma are benign tumours arising from Schwann cells. Schwannoma of superficial radial nerve is very rare. We report a 22 years old female who presented with a painless swelling on the dorsum of the hand simulating clinically a lipoma. Excision of the swelling was performed and on histopathological examination it proved to be Schwannoma. So, while dealing with any lump over dorsum of the hand in the distribution of superficial radial nerve Schwannoma should be kept in mind as one of the differential diagnoses and proper radiological evaluation before excision of swelling should be routinely done followed by histopathological confirmation and immunohistochemistry.